P319 Attitude towards paediatric use of natural medicines: a cross-country survey conducted in general paediatrics. (6th June 2017) - Huckstadt, MP Riveros; Beer, AM; Burlaka, I; Buskin, S; Kamenov, B; Pettenazzo, A; Popova, D; Sakalinskas, V; M, Oberbaum
Abstract : Background and aims: The use of CAM (Complementary and Alternative Medicine) in paediatrics is high, although a variability of usage frequency between countries is reported, depending on data collection methods and type of CAM. The aim of this survey was to look into physicians' approaches towards paediatric use of natural medicines, by a consistent study approach in a multi-country survey. Methods: On-line survey involving 582 general paediatricians and general practioners treating paediatric patients in 6 countries. The study was sponsored by DHU-Arzneimittel GmbH and Co. KG. Results: 99% of respondents recommended natural medicines (Phytotherapy or vitamins/minerals/supplements, VSM) in the previous year. Natural medicines were used as a complement to conventional treatment in most of patients. The most frequently treated conditions were: upper respiratory tract infections (51%), allergies (22%), acute abdominal problems (22%), recurrent infections (22%), earache (17%) and infant colic (15%). Here we give summarised data about the trends in natural remedies prescriptions by paediatricians. In the case of a 2 month old infant with recurrent colic 80% of physicians advised dietary changes. Conventional drugs were as frequently recommended as phytotherapy or homeopathy. The therapy of choice was probiotics. For a 2 year old child with teething problems, homeopathy was advised by 30% of physicians, while only 25% recommended conventional drugs. For a 5 year old child with recurrent upper respiratory tract infections the most frequent recommendations were conventional drugs, dietary advice and vitamins. Personal use of natural medicines corresponded to physicians´ predisposition to recommend natural treatments for their paediatric patients. Nearly half of the physicians were extremely interested in phytotherapy for paediatric conditions. Conclusions: This survey confirms that physicians have a high interest in using natural medicines in paediatrics. Natural medicines were most often prescribed alongside conventional drugs. There is evidence of a variable level of knowledge about natural medicine options. There were significant country differences showing a cultural influence on physicians' decisions.